Race and Stratification in College Enrollment Over Time. (January 2018) - Baker, Rachel; Klasik, Daniel; Reardon, Sean F.
We measure college enrollment selectivity gaps by race-ethnicity using a novel method that is sensitive to both the level (2- vs. 4-year) and selectivity of the college in which students enroll. We find that overall Hispanic–White and Black–White enrollment selectivity gaps closed in the United States between 1986 and 2014. This overall closing of gaps appears to be related to the closing of high school graduation gaps. However, this contraction was driven almost entirely by students at the margin between no college and college enrolling in non-degree-granting programs. Among students who enrolled in degree-granting schools, Black students have enrolled at increasingly less selective institutions than White students, whereas Hispanic–White gaps remained relatively unchanged over the nearly 30 years of our study. These gaps are concerning because of their implications for long-term economic inequality.